Male and Female Family Social Addresses in The Minangkabau Tribes of Sumatera Barat, Indonesia - Rasyimah Rasyimah; Fachri Yunanda (English Teaching and Linguistics Journal (ETLiJ), 2022)
The focus of this research is on male and female family social addresses in Minangkabau Tribe of Sumatera Barat in Indonesia. The purpose of this study is to examine Minangkabau people's social addresses. The research approach employed in this study was descriptive qualitative. The results of interviews with Minangkabau people were analyzed in this study. As a consequence, Minangkabau people employed twenty five male and female addresses in their family interactions. This addressee is used to indicate the degree of social status, as well as to convey respect for the eldest family member and affection for the youngest.